Abnormalities of brain gray matter in bipolar depression and unipolar depression - Zhou, Li; Wu, Guowei; Li, Xinchun; Liu, Chang (Frontiers in Psychology, 2025)
ObjectiveWe sought to investigate differences in gray matter (GM) volume among patients with bipolar depression (BD), unipolar depression (UD), and healthy controls (HCs) to identify distinct gray matter volume abnormality patterns that may help differentiate BD from UD.MethodsIn total, 23 patients with BD, 22 patients with UD, and 24 HCs were recruited to undergo dimensional, structural magnetic resonance imaging. Using voxel-based morphometry (VBM), we investigated gray matter volume across the three groups.ResultsBoth patient groups showed significantly reduced gray matter volume in the right superior temporal gyrus and right insula compared to the HCs. Moreover, the right posterior cingulate cortex exhibited decreased gray matter volume in the BD group but increased gray matter volume in the UD group. In addition, gray matter reductions in the right superior temporal gyrus and right insula were significantly positively correlated with the total Hamilton Depression Rating Scale (HAMD) score in the UD group.ConclusionPatients with BD and UD demonstrate different patterns of gray matter abnormalities in the right posterior cingulate cortex, which might be a biomarker for differentiating these two depressive disorders.